The use of linguistic materials in teaching Ukrainian as a foreign language (Pedagogy of Higher and Secondary Education, 2012)
Maksymenko H. A. The use of linguistic materials in teaching Ukrainian as a foreign language.The article is devoted to the problem of using linguistic-geographical materials in teaching process of foreign students the Ukrainian language. The author proves the necessity of using texts, that contain linguistic-geographical information, author outlines the selecting criteria for linguistic-geographical texts, gives examples of working with the texts.
Keywords: linguistic-geographical material; foreign students; Ukrainian language; sociolinguistic competence